The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1103/physrevlett.122.205301
|View full text |Cite
|
Sign up to set email alerts
|

Variational Approach for Impurity Dynamics at Finite Temperature

Abstract: We present a general variational principle for the dynamics of impurity particles immersed in a quantum-mechanical medium. By working within the Heisenberg picture and constructing approximate time-dependent impurity operators, we can take the medium to be in any mixed state, such as a thermal state. Our variational method is consistent with all conservation laws and, in certain cases, it is equivalent to a finite-temperature Green's function approach. As a demonstration of our method, we consider the dynamics… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 46 publications
6
90
0
Order By: Relevance
“…A intriguing aspect would be to examine whether thermalization of the impurities dynamics takes place for strong repulsions in the framework of the eigenstate thermalization hypothesis [101]. An imperative prospect is to study the robustness of the emergent quasiparticle picture in the current setting in the presence of temperature effects [102,103]. Moreover, the study of induced interactions of two bosonic impurities immersed in a Fermi sea would be an interesting prospect especially in order to expose their dependence on the different statistics of the medium.…”
Section: Discussionmentioning
confidence: 99%
“…A intriguing aspect would be to examine whether thermalization of the impurities dynamics takes place for strong repulsions in the framework of the eigenstate thermalization hypothesis [101]. An imperative prospect is to study the robustness of the emergent quasiparticle picture in the current setting in the presence of temperature effects [102,103]. Moreover, the study of induced interactions of two bosonic impurities immersed in a Fermi sea would be an interesting prospect especially in order to expose their dependence on the different statistics of the medium.…”
Section: Discussionmentioning
confidence: 99%
“…At finite temperature, we investigate the full spectral function of the Bose polaron within our variational approach [41]. Including all two-body correlations involving the impurity and a bosonic excitation, we recover the results of Ref.…”
Section: Introductionmentioning
confidence: 92%
“…The framework for our investigation of the Bose polaron at finite temperature is the variational approach for impurity dynamics first developed in Ref. [41] in the context of Fermi polarons. A variational method based on including only one excitation of the medium was first used to obtain the zero-temperature ground-state properties of the Fermi polaron [50] as well as the repulsive branch [51,52], and it has been demonstrated that such an approach is equivalent to a diagrammatic formulation [53].…”
Section: Variational Approachmentioning
confidence: 99%
See 2 more Smart Citations